Child Witnesses Productively Respond to "How" Questions About Evaluations but Struggle With Other "How" Questions. (August 2023) - Henderson, Hayden; Sullivan, Colleen E.; Wylie, Breanne E.; Stolzenberg, Stacia N.; Evans, Angela D.; Lyon, Thomas D.
Child interviewers are often advised to avoid asking "How" questions, particularly with young children. However, children tend to answer "How" evaluative questions productively (e.g., "How did you feel?"). "How" evaluative questions are phrased as a "How" followed by an auxiliary verb (e.g., "did" or "was"), but so are "How" questions requesting information about method or manner (e.g., "How did he touch you?"), and "How" method/manner questions might be more difficult for children to answer. We examined 458 5- to 17-year-old children questioned about sexual abuse, identified 2485 "How" questions with an auxiliary verb, and classified them as "How" evaluative ( n = 886) or "How" method/manner ( n = 1599). Across age, children gave more productive answers to "How" evaluative questions than "How" method/manner questions. Although even young children responded appropriately to "How" method/manner questions over 80% of the time, specific types of "How" method/manner questions were particularly difficult, including questions regarding clothing, body positioning, and the nature of touch. Children's difficulties lie in specific combinations of "How" questions and topics, rather than "How" questions in general.